AUDITORÍA DE GESTIÓN AL HOSPITAL BÁSICO 7-BI LOJA, PERÍODO 01 DE ENERO AL 31 DE DICIEMBRE DEL 2014 - Puglla Castillo, Mónica Elizabeth (2016)
The research work entitled "AUDIT OF HOSPITAL MANAGEMENT BASIC 7-BI Loja, PERIOD 01 JANUARY TO 31 DECEMBER 2014" was held to meet a requirement of the National University of Loja, prior to choose an Engineering degree in Accounting and Audit Certified Public Accountant - Auditor and for compliance with the following specific objectives were raised. The first specific objective is to "assess the internal control system and the degree of achievement of goals and objectives of the Basic Hospital 7-BI Loja by applying a management audit", which was developed through the application of the questionnaire Hospital internal control and get to know the strengths and weaknesses within this prestigious House of Health. The second specific objective is to "apply management indicators that permit evaluation of its components", you will be executed based on the application of indicators of efficiency, effectiveness and economy, the Administrative and Operational components coming to determine the reliability and reasonableness with which their functions and activities are developed. The third specific objective is to "prepare a report containing conclusions and reasonable and appropriate recommendations to support decision making to optimize institutional management", recorded at the end of the 5 audit report led to management to take corrective measures allowed to improve management and in this way contribute to the development of this prestigious House of Health. To fulfill the objectives it was necessary to compile the information that was begun with the preliminary audited entity knowledge, the development of the audit program and then apply the internal control questionnaires; the same that were evaluated, analyzed and helped to know the weaknesses and then issuing the respective conclusions and recommendations for achieving organizational performance. At the end of the thesis by assessing the internal control system, it was determined deficiencies in internal control, the main listed; does not have a manual functions approved, lack of implementation of indicators, inadequate physical infrastructure, a shortage of doctors in various specialties and supplies and materials are not appropriate, whereby the respective recommendations were made to improve the administration of this prestigious House of Health.